PENGEMBANGAN MEDIA PEMBELAJARAN HYPERLINK BERBASIS CANVA PADA MATA PELAJARAN AKIDAH AKHLAK MATERI ASMAUL HUSNA KELAS X DI MAS MUSLIMAT NU PALANGKA RAYA - Ihsan Auliya Arrasyid; Cindy Elvira; Nur Asyifa Ananda; Abdul Azis (CV. ADIBA AISHA AMIRA, 2024)
This research aims to develop Canva-based hyperlink learning media for the subject of Asmaul Husna's Aqidah Moral material for class X MAS Muslimat NU Palangka Raya. This development was motivated by the limited learning media used in schools, which only relied on textbooks and simple PowerPoints, causing a lack of motivation and student activity in learning. The research methodology uses a Research and Development (R&D) approach with a 4-D development model (Define, Design, Develop, Disseminate). Data was collected through questionnaires and interviews, involving validation from material and media experts, as well as assessments from subject teachers and student responses. The validation results show a high level of feasibility, with a percentage of 88% from material experts and 80% from media experts. The subject teacher assessment reached 81.67% in the